1982
DOI: 10.1073/pnas.79.17.5406
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic fuel and amino acid transport into the brain in experimental diabetes mellitus.

Abstract: We used the Oldendorf brain uptake index method to study the blood-brain barrier transport of several metabolic substrates in diabetes. Glucose transport into the brain was decreased by 1/3 in rats with moderate diabetes induced by prior injection of streptozotocin (65 mg/kg of body weight). The transports of mannose and the poorly metabolized hexoses 2-deoxyglucose and 3-0-methylglucose were similarly reduced. Likewise, brain glucose transport was decreased in rats with alloxan-induced diabetes. These alterat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
61
3
1

Year Published

1983
1983
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(71 citation statements)
references
References 19 publications
6
61
3
1
Order By: Relevance
“…However, the extent to which brain metabolism in diabetics is similar to that of normal subjects is presently unknown. Since the antecedent glycemic level influences brain glucose transport, i.e., chronic hyperglycemia reduces (39,40) and chronic hypoglycemia increases (41) glucose transport to the brain, the results of the present study in normal nondiabetic subjects do not necessarily establish the glycemic threshold for onset of neuroglycopenia, activation of counterregulatory hormones and symptoms of hypoglycemia in diabetic patients. Actually, it has been shown that the glycemic threshold for activation of counterregulation and symptoms of hypoglycemia is increased in diabetic subjects chronically hyperglycemic (42), whereas it is decreased in diabetics treated with regimens of intensive insulin therapy (42)(43)(44)(45)(46)(47) which result in chronically subnormal plasma glucose concentrations (48).…”
Section: -E _ 150-mentioning
confidence: 65%
“…However, the extent to which brain metabolism in diabetics is similar to that of normal subjects is presently unknown. Since the antecedent glycemic level influences brain glucose transport, i.e., chronic hyperglycemia reduces (39,40) and chronic hypoglycemia increases (41) glucose transport to the brain, the results of the present study in normal nondiabetic subjects do not necessarily establish the glycemic threshold for onset of neuroglycopenia, activation of counterregulatory hormones and symptoms of hypoglycemia in diabetic patients. Actually, it has been shown that the glycemic threshold for activation of counterregulation and symptoms of hypoglycemia is increased in diabetic subjects chronically hyperglycemic (42), whereas it is decreased in diabetics treated with regimens of intensive insulin therapy (42)(43)(44)(45)(46)(47) which result in chronically subnormal plasma glucose concentrations (48).…”
Section: -E _ 150-mentioning
confidence: 65%
“…The finding that diabetes has an effect on transport in central axons is not surprising, since there is a large body of evidence that in diabetes both metabolism and functions of the central nervous system are affected (37)(38)(39). The paucity of clinical signs of central nervous system involvement in diabetes (40,41) may be explained on the basis of a preferential vulnerability of peripheral over central axons that is also observed in certain toxic conditions (27) Another finding of the present study is that the crosssectional area of the sciatic axons in diabetic animals is increased in the proximal segments, normal in the intermediate region, and decreased distally (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Twelve normal humans were studied over 4 days. (6). Based on the preceding series of facts, we presume that in sustained human hypoglycemia, normal increments in epinephrine and glucagon will fail to occur, reflecting a normalization ofglucose availability to the brain secondary to improved glucose uptake.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic changes in the antecedent level ofglycemia (either sustained hyperglycemia or hypoglycemia) induce alterations in brain glucose metabolism in rodents. Chronically hyperglycemic animals experience low fractional extraction (and presumably reduced transport capacity), while animals with diabetes treated to reduce their glucose levels toward normal have relatively higher fractional rates of glucose extraction (6). Based on the preceding series of facts, we presume that in sustained human hypoglycemia, normal increments in epinephrine and glucagon will fail to occur, reflecting a normalization ofglucose availability to the brain secondary to improved glucose uptake.…”
mentioning
confidence: 98%